Swimming in the monsoon sea - Selvadurai, Shyam, 1965- (Tundra Books, 2022)
The setting is Sri Lanka, 1980, and it is the season of monsoons. Fourteen-year-old Amrith is caught up in the life of the cheerful, well-to-do household in which he is being raised by his vibrant Aunty Bundle and kindly Uncle Lucky. He tries not to think of his life "before," when his doting mother was still alive. Amrith's holiday plans seem unpromising: he wants to appear in his school's production of Othello and he is learning to type at Uncle Lucky's tropical fish business. Then, like an unexpected monsoon, his cousin arrives from Canada and Amrith's ordered life is storm-tossed. He finds himself falling in love with the Canadian boy. Othello, with its powerful theme of disastrous jealousy, is the backdrop to the drama in which Amrith finds himself immersed.